1987
DOI: 10.1113/jphysiol.1987.sp016543
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐adrenergic blockade restores glucose's antiketogenic activity after exercise in carbohydrate‐depleted athletes.

Abstract: SUMMARY1. The development of post-exercise ketosis is not abolished by the ingestion of glucose immediately after exercise, despite inducing high insulin/glucagon ratios in the peripheral (and therefore by implication in the portal) blood.2. To investigate the possibility of autonomic control of the liver influencing its sensitivity to the major counter-regulatory hormones, we administered 50 g glucose, either on its own, or together with 0 5 mg prazosine, 40 mg propranolol, or 15 mg propantheline, to forty-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The high degree of correlation between the blood ketone body concentration and simultaneous liver glycogen content (r = -0-88) suggests that the link between the two is very close indeed after exercise. Such a close link has never previously been shown to exist between the post-exercise blood ketone body concentration and any other biochemical variable measured to date (Johnson et al 1969 a, b;Johnson & Rennie, 1973;Winder et al 1973;Rennie et al , 1976Holloszy et al 1978;Koeslag et al 1980Koeslag et al , 1982Koeslag et al , 1985Beattie et al 1985;Adams et al 1987;Adams & Koeslag, 1989). The nature of the link, and the mechanisms which drive the system, remain matters for speculation beyond the scope of this article.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The high degree of correlation between the blood ketone body concentration and simultaneous liver glycogen content (r = -0-88) suggests that the link between the two is very close indeed after exercise. Such a close link has never previously been shown to exist between the post-exercise blood ketone body concentration and any other biochemical variable measured to date (Johnson et al 1969 a, b;Johnson & Rennie, 1973;Winder et al 1973;Rennie et al , 1976Holloszy et al 1978;Koeslag et al 1980Koeslag et al , 1982Koeslag et al , 1985Beattie et al 1985;Adams et al 1987;Adams & Koeslag, 1989). The nature of the link, and the mechanisms which drive the system, remain matters for speculation beyond the scope of this article.…”
Section: Discussionmentioning
confidence: 97%
“…We confined our enquiry to the measurement of the blood 3-hydroxybutyrate and tissue glycogen concentrations because we could only obtain very small quantities of blood from each rat with certainty, and because the plasma hormone, glucose, free fatty acid, and acetoacetate concentrations have already been studied exhaustively without leading to clear conclusions (Johnson et al 1969a, b;Johnson, Rennie, Walton & Webster, 1971;Johnson & Walton, 1972;Johnson & Rennie, 1973;Winder et al 1973;Rennie, Winder & Holloszy, 1976;Holloszy, Winder, Fitts & Rennie, 1978;Koeslag, Noakes & Sloan, 1980, 1982Beattie & Winder, 1984Koeslag, Levinrad, Lochner & Sive, 1985;Adams, Irving, Koeslag, Lochner, Sandell & Wilkinson, 1987). The effects of dietary manipulation on the tissue glycogen levels and post-exercise ketosis are described elsewhere (Adams & Koeslag, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The hormones which might influence the development of post-exercise ketosis have been shown to act paradoxically during the recovery from exercise (Koeslag, Noakes & Sloan, 1982;Koeslag, Levinrad, Lochner & Sive, 1985;Adams, Irving, Koeslag, Lochner, Sandell & Wilkinson, 1987), and to change with the diet in the same way that post-exercise ketosis changes with the previous day's carbohydrate intake (Koeslag et al 1980). The present findings therefore support the hypothesis that the availability of mobilizable carbohydrate after exercise is an important (but probably not the sole) determinant of the development of post-exercise ketosis.…”
Section: Discussionmentioning
confidence: 99%
“…Their breakdown products are 3-hydroxyacids, which are naturally found in animals. Such as PHB is biocompatible, which is not surprising when considering the fact that R-3-hydroxybutyric acid is a normal constituent of blood at concentrations between 0.3 and 1.3 mM (31,205,206) and is also found in the cell membrane of eukaryotes (207). These PHAs have the potential to become important and very useful compounds for medical applications such in wound management used as surgical suture, skin substitutes, nerve cuffs, surgical meshes, implants, gauzes, staples, gauzes, swab, lubricating powders (29,30,38), blood vessels, tissue scaffolds and bone fracture fixation plates (3,251,252).…”
Section: (2) Medical and Pharmaceutical Applicationsmentioning
confidence: 99%
“…A number of studies have shown that PHB take part in formation of transmembrane ion channel complexes in eukaryotic and prokaryotic cell membranes (31,(205)(206)(207). Interestingly, degradation of PHB polymer results ultimately in the production of, R-3-hydroxybutyric acid which also is a normal constituent of blood at concentrations between 0.3 and 1.3 mM and known to be associated with ketone body formation.…”
Section: In Vivo Biocompatibilitymentioning
confidence: 99%